PCM-based solar collectors for thermal energy storage - Han, Jeremy Mingguang. (2010)
Increasing awareness of environmental issues and climate change has led to the build-up of the renewable energy industry. As such, water heating is one major area which can be tapped to harness solar energy. The objective of this report is to assess the potential application in instantaneous water heating whereby an integrated flat plate solar collector is designed, fabricated and tested. In this study, tests on three systems, one in which the heat storage material is made of Phase Change Material (PCM) and the other two with water and air, will be carried out to measure the difference between the inlet and outlet water temperature and hence, heat gain and efficiency of the collector system. The effects of different heat storage medium and water flow rates were examined. From the experimental results, the three heat storage medium were compared and it was found that PCM has the best heat retention properties along with the highest fin temperature and water outlet temperature after sunset. Flowrate analysis also presented that a higher flowrate improves the system performance and efficiency as measured by the performance ratio. Although PCM has the best performance in terms of efficiency and as heat storage medium, economical considerations such as cost of PCM material and high flowrates along with long payback time may deter the use and application of the integrated solar collector system.